Major Bifurcations, Slip Rates, and A Creeping Segment of Sumatran Fault Zone in Tarutung-Sarulla-Sipirok-Padangsidempuan, Central Sumatra, Indonesia - Danny Hilman Natawidjaja (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.2.137-160A detailed active fault study in Tarutung-Sarulla-Sipirok-Padangsidempuan was conducted based on their tectonic-morphological features using SRTM-30, 3D-visualization, and LIDAR data, combined with field and shallow geophysical surveys using the GPR method. Sumatran Fault Zone is bifurcated from the single major Sianok fault segment into two major branches: Angkola and Barumun-Toru Faults that run (sub) parallel to each other. In the studied area, they are merged gradually to become the Renun Fault. The total slip rates from Sianok to Renun segments are constant at about ~ 14 mm/year (13.8 ± 0.3 mm/yr on Renun and 13.7 ± 1.6 mm/yr on Sianok segments). In the bifurcation zone, it is partitioned into 9.3 ± 1.8 mm/yr slip on Toru, and about 4 - 5 mm/yr on Angkola segments. Based on field evidence supported by the seismicity and historical record, the Toru Fault appears to move continuously (creeping). This is crucial for understanding tectonics and its significance to hazard mitigations. Further investigations on Angkola and Toru Faults are crucial for mega installations of Sarulla Geothermal Power Plant, which is located in between Angkola and Toru Fault zones.